The Role Of Therapeutic Simulators In Education: Enhancing Learning And Skill Development - Salimova Nargiza Djurabaevna; Salaeva Muborak Saidobdullaevna; Ergashov Nodirbek Shermukhamat ugli (Genius Journals, 2024)
Therapeutic simulators, particularly those utilizing Virtual Reality (VR) and Augmented Reality (AR), are transforming education in healthcare and therapy fields by providing immersive, hands-on learning experiences. These advanced technologies enable students to practice complex procedures, engage in realistic therapeutic scenarios, and receive real-time feedback, all within a controlled, risk-free environment. VR and AR offer significant advantages, including the ability to simulate rare cases, improve patient interaction skills, and develop critical decision-making abilities. These tools are also costeffective, scalable, and increasingly accessible, making high-quality training available to a broader range of learners. As the technologies evolve, they are expected to become even more interactive and personalized, further enhancing the effectiveness of therapeutic education. This article explores the role of VR and AR in therapeutic simulators, highlighting their current applications, benefits, challenges, and potential for future advancements.
Keywords: Therapeutic simulators; Virtual Reality; Healthcare education